Improved voltage transfer method for lithium battery string management chip - Kai‐Kai Wu; Hong‐Yi Wang; Chen Chen; Tao Tao; You‐You Fan; Hao Zhang; Yu‐Xin Liu (IET Circuits, Devices and Systems)
Abstract In order to cut the costs and overcome the leakage current of batteries caused in traditional method, this study introduces an improved voltage transfer method for lithium battery string management chip. This proposed circuit based on the improved voltage transfer method is fabricated in 180‐nm Bipolar‐CMOS‐DMOS is correct technology, and has been successfully applied to a three lithium batteries string management chip. These measurements indicate that this circuit transfers each cell’s voltage reliably and adopt protection against abnormal conditions. Furthermore, analysis of 50 samples shows that the improved method can greatly eliminate the battery leakage. The circuit reduces the leakage current to nanoampere scale and is integrated into the lithium battery string management chip, which is helpful for battery voltage balance and low cost.